The Essence and Content of Cybercrime in Modern Times - ALMAZKYZY, Karlygash; ESTEUSIZOV, Yernar N. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9.3(33).05, 2018)
This article discusses the main characteristics of cybercrime as a new criminal threat to modern society. The authors attempted to explain the appearance of a new type of crime in the period of development and implementation of high technologies in all spheres of life of the world community. Using the dialectical method of cognition, as well as formal logical methods, steps in order to develop the conceptual apparatus of the investigated phenomenon of cybercrime were taken. Such terms as ‘cyberspace’ and ‘cybersecurity’ acquired the authors' explanations. According to the authors, criminality in cyberspace has been one of the most difficult problems of the international community in recent years due to the development of information and communication technologies. The article analyzes the phenomenological aspects of criminality in global information networks, discusses the definition of ‘cybercrime’, and considers the current trends in its development. Revealing the essence of the investigated type of crime, the authors analyzed the content and marked the differences of cybercrime from Internet crime, computer crime, crime in the information sphere, etc. The authors analyzed the modern normative, scientific and expert approaches to the study of the structure and state of cybercrime in the Republic of Kazakhstan. The results of the study and the conclusions of this article can be used as a theoretical contribution to the enrichment and expansion of scientific vision of cybercrime at the formation of approaches and the system of existing views, forming the concept of criminological security, and can also serve to further development of scientific ideas in the sphere of criminal law and criminological provision of prevention of cybercrime.